Moderating role of live microbe between chronic inflammatory airway disease and depressive symptoms - Li, Wenqiang; He, Qian; Bai, Jingshan; Wen, Youli; Hu, Zefu; Deng, Zhiping; Huang, Qian (Frontiers in Nutrition, 2025)
PurposeOur study aims to investigate the impact of dietary live microbe on the relationship between chronic inflammatory airway diseases (CIAD) and depressive symptoms.MethodsWe selected data from the NHANES database from 2007 to 2020. First, we explored the relationship between CIAD and depressive symptoms using logistic regression analysis. And subgroup analyses were conducted to demonstrate the relationship and whether there was an interaction effect between the two in each subgroup. Then, we further analyzed the effect of live microbe on depressive symptoms in CIAD patients. And subgroup analyses were conducted to assess whether the effect of dietary viable microbial levels on depressive symptoms held true in each subgroup and whether there was an interaction effect.ResultsA study included 23,072 participants, of whom 5,111 were diagnosed with CIAD, and 5,110 had live microbial information available. Multivariate logistic regression analysis revealed that, compared to those without CIAD, individuals with CIAD had an increased risk of depressive symptoms. Subgroup analysis indicated that, except for educational level and smoking status, all other subgroups demonstrated that CIAD increased the risk of depressive symptoms. Additionally, within the CIAD population, a higher level of live microbe was associated with a reduced risk of depressive symptoms. It is implied that live microbe can negatively modulate the relationship between CIAD and depressive symptoms. Subgroup analysis further showed no significant interaction effects across subgroups (p > 0.05).ConclusionChronic inflammatory airway diseases can increase the risk of developing depressive symptoms. Dietary live microbe negatively modulate the relationship between CIAD and depressive symptoms. High levels of dietary live microbe significantly reduced the risk of depressive symptoms in patients with CIAD.